From A Colonial to A National Company: The Nationalization of Western Private Plantation in Indonesia - Wasino wasino (Lembaran Sejarah, 2017)
This paper discusses the nationalization of Dutch-owned enterprises in post-colonial Indonesia in a process termed Indonesianisasi. It looks at the legal framework necessary for the transfer of assets. It also looks into the process of nationalization in some companies and the regulations created in order to create a semblance of due process.